SPEECH FUNCTION IN THE WITHDRAWAL SPEECH OF PRABOWO-HATTA ON THE INDONESIA PRESIDENTIAL ELECTION 2014-2019 - Hasbi Ramadhan and Meisuri (LINGUISTICA, 2015)
The study deals with the types of speech function used in the withdrawal speechof Prabowo-Hatta on the Indonesia presidential election 2014-2019. Theobjectives of this research were to find out the types of speech function and todescribe the implication of the most dominant type of speech function. Thisresearch was conducted by using descriptive qualitative design. The data were 55clauses taken from the withdrawal speech of Prabowo-Hatta on the Indonesiapresidential election 2014-2019 which were collected by applying documentarytechnique. The three types of speech function occurred in this speech, namelystatement (87,3%) , offer (1,8%), and command (10,9%). The most dominant typeof speech function was statement. The implication of using statement dominantlywas Prabowo-Hatta can declare all of aspects that they consider as their evidencesthat to prove their argumentation to withdraw from Indonesia presidential election2014-2019. The dominant statement also made more powerful speech to influencethe public opinion that will realize Prabowo-Hatta has already known about theincident occurred in Indonesia Presidential Election 2014-2019. It can beillustrated through the use of statement by Prabowo-Hatta that is in a practiceconsidered as a representative of a power to state a strong degree of certainty.